Dinamika Epistemologi Bayani, Burhani, dan Irfani Dalam Pembelajaran Agama Anak Usia Dini - Sulton Agung; Umu Sa'diyah; Moh. Afifur Rohman Romli (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2026)
This qualitative case study analyzes the epistemological tendencies of early childhood (5-6 years) in Raudhatul Athfal Ashfiyah in understanding the basic concepts of Islam sourced from the book Fath al-Qarib through learning observations, interviews with teachers, and analysis of learning documents. The results show that the process of construction of early childhood religious knowledge moves on an adaptive epistemological spectrum according to the stages of their cognitive development. Bayani epistemology (textual-narrative) emerges through a pattern of story learning and modeling, in which children receive basic fiqh knowledge through simple narratives taken from Fath al-Qarib. Question-based learning methods and role-playing simulations facilitate the emergence of Burhani Epistemology in the form of concrete cause-and-effect reasoning. The Elements of Irfani's Epistemology are present through the concrete spiritual experiences of children during the practice of worship together and the formation of spiritual habits. The epistemic system of early childhood is spiral-gradual: it begins with narrative acceptance, progresses to experiential, concrete reasoning, and is reinforced through spiritual habituation in daily routines. In conclusion, the epistemology of religious learning for early childhood is not purely passive-imitative, but evolves progressively through the interaction between textual narratives, teacher modeling, children's concrete exploration, and direct spiritual experiences that correspond to their concrete pre-operational developmental stages